2014
DOI: 10.7860/jcdr/2014/8991.4711
|View full text |Cite
|
Sign up to set email alerts
|

Visual loss in Takayasu Arteritis – Look Beyond the Eye

Abstract: A 32-year-old woman with history of inflammatory arthritis, presented with transient right focal seizures followed by blurred vision that resolved completely, two months prior to presentation to our hospital. A further short, self-limiting episode occurred two weeks later. On examination both upper limb blood pressures were not recordable. Systemic examination was otherwise normal. Erythrocyte sedimentation rate was 45mm at one hour, C-reactive protein was 10.4mg/L and anti-nuclear antibody was negative. Magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…6 The loss of vision may be acute or chronic, transient or permanent, partial or total, or may be just linked to the disease severity at presentation. 9 This was reaffirmed in this study, as patients with relentlessly progressive disease showed progressive vision deterioration.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…6 The loss of vision may be acute or chronic, transient or permanent, partial or total, or may be just linked to the disease severity at presentation. 9 This was reaffirmed in this study, as patients with relentlessly progressive disease showed progressive vision deterioration.…”
Section: Discussionsupporting
confidence: 78%
“…These symptoms occur due to embolism in the retinal artery. Acute onset of permanent visual loss may occur with embolic occlusion of the central or branch retinal artery, venous occlusion, anterior ischemic optic neuropathy and vitreous hemorrhage 9 Extension of the neck in a few of these patients may precipitate visual disturbances. 11 This case series did not find neurological complications or stroke in any of the patients when they presented to the ophthalmic clinic.…”
Section: Discussionmentioning
confidence: 99%
“…5 Other reported manifestations include central or branch retinal artery or vein occlusion; anterior ischaemic optic neuropathy; vitreous haemorrhage secondary to neovascularisation; neovascular glaucoma; or uveitis. 6 We report the first case of TA diagnosed following initial presentation with bilateral occlusive retinal vasculitis. This rare manifestation of TA was reported in one other case of a patient with a diagnosis of TA referred to the ophthalmology clinic.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with carotid artery involvement encounter decreased retinal perfusion leading to chronic ocular ischemia. Ocular ischemic syndrome and related ocular manifestations such as retinal microaneurysms, microhemorrhages, branch retinal vein occlusion, proliferative retinopathy, cataract, neovascular glaucoma, ischemic optic neuropathy, retinal detachment, and optic atrophy in TA were reported previously [13]. …”
Section: Introductionmentioning
confidence: 89%
“…It is an unusual and idiopathic disease that affects aorta and its branches and causes constriction and obliteration [13]. The disease involves especially subclavian arteries and aortic branches but can affect any arteries.…”
Section: Introductionmentioning
confidence: 99%